2013
DOI: 10.1002/ejic.201300878
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear Cage‐Like Copper(II) Silsesquioxane (“Cooling Tower”) – Its High Catalytic Activity in the Oxidation of Benzene and Alcohols

Abstract: A new method of metallasilsesquioxane synthesis is described for the first time. According to this method, a partial nucleophilic cleavage of polymeric copper phenylsilsesquioxane by the use of sym-cis-tetraphenylcyclotetrasiloxanolate nonaethanolate (1) gave previously unknown binuclear cage-like copper silsesquioxane [(PhSiO 1.5 ) 10 (CuO) 2 (NaO 0.5 ) 2 ·

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 55 publications
0
30
0
Order By: Relevance
“…Polynuclear metal complexes containing voluminous organic [63,66,118,119,[129][130][131]186,[213][214][215][216][217][218][234][235][236][237][238][239][240][241] or siloxane [221][222][223][224][225][226][227][228] ligands are also very efficient in oxidations of organic compounds including saturated hydrocarbons with peroxides. For example, dinuclear copper complex 11 [221,224] and hexairon complex 15 (for the structure, see Figure 9) affording the products of cyclohexane oxidation in a very high yield of 46% (see Figure 10 [226]) can be considered as "inorganic models of methane monooxygenases."…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Polynuclear metal complexes containing voluminous organic [63,66,118,119,[129][130][131]186,[213][214][215][216][217][218][234][235][236][237][238][239][240][241] or siloxane [221][222][223][224][225][226][227][228] ligands are also very efficient in oxidations of organic compounds including saturated hydrocarbons with peroxides. For example, dinuclear copper complex 11 [221,224] and hexairon complex 15 (for the structure, see Figure 9) affording the products of cyclohexane oxidation in a very high yield of 46% (see Figure 10 [226]) can be considered as "inorganic models of methane monooxygenases."…”
Section: Discussionmentioning
confidence: 99%
“…For example, dinuclear copper complex 11 [221,224] and hexairon complex 15 (for the structure, see Figure 9) affording the products of cyclohexane oxidation in a very high yield of 46% (see Figure 10 [226]) can be considered as "inorganic models of methane monooxygenases." These enzymes contain dinuclear copper [317,318] and iron [319] reaction centers, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most popular method for preparation of cyclic siloxane monomers is hydrolytic condensation of trialkoxyorganosilanes (Scheme 1) in the presence of water and an alkali metal hydroxide. It was found that properties of metal cations can influence the structure of the formed moieties since they work as template centers and structural elements helping to bind siloxane bonds into cyclic organosiloxanolate fragments [20][21][22][23][24][25][26][27][28][29][30][31][32]. While transition or rare-earth metal cations lead to the formation of varied-size (n=4 [20], 5 [21], 6, 8, 12 [22][23][24]) cyclic species, sodium and potassium cations enable the synthesis of small cyclosiloxanes containing three [25][26][27][28] or four [29][30][31] silicon atoms.…”
Section: Introductionmentioning
confidence: 99%